Prevalence and appropriateness of omeprazole prescription in dogs at a veterinary teaching hospital before and after the publication of the ACVIM consensus statement on the rational administration of gastrointestinal protectants - Sainz, Ángel; García-Sancho, Mercedes; Villaescusa, Alejandra; Rodríguez-Franco, Fernando; Díaz-Regañón, David; Olmeda, Patricia; Marks, Stanley L. (Frontiers in Veterinary Science, 2024)
Introduction Overprescribing of acid suppressants is a common phenomenon in human and small animal patients, leading to potential deleterious gastrointestinal (GI) and non-GI consequences. The impact of consensus statements on veterinary prescribing habits in clinical practice have not been fully evaluated. This study aimed to compare the prescribing habits of the proton pump inhibitor (PPI), omeprazole, in dogs in an academic veterinary teaching hospital before and after the publication of the American College of Veterinary Internal Medicine (ACVIM) consensus statement on rational use of gastrointestinal protectants. Methods Evaluation of the prescribing habits of omeprazole in dogs during the years 2017 and 2021 was retrospectively compared. These years were selected to reflect a 12-month period prior to and following the publication of the consensus statement. One hundred dogs from each year were randomly selected. Dose, frequency of administration, duration of treatment, concurrent prescription of more than one gastroprotectant and indications for prescribing omeprazole were analyzed. Results A significant increase in the cases that received omeprazole q12h (p < 0.0001) or that underwent a tapering dose after ≥4 week-therapy (p > 0.0001) was detected after the publication of the 2018 ACVIM consensus statement. Considering the indications, there was also a significant increase in the appropriate prescription of omeprazole in the second compared to the first period of study (p < 0.0001). Fifteen of 16 clinicians (94%) involved in the prescription of omeprazole indicated that their reading of the consensus statement had changed their clinical practice regarding PPI administration in dogs. Discussion These results support the beneficial impact of the ACVIM consensus statement on the judicious prescribing of omeprazole in an academic veterinary hospital. These results should not be extrapolated to first-opinion veterinary practices, and further efforts should be made to ensure that PPIs are prescribed prudently with a clear indication and regular review of the appropriateness of continued administration to minimize possible risks and adverse drug interactions.